Interventions in labour markets: An overview - Juergen B. Donges; Dean Spinanger (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1983)
The starting point of this overview is the contention that unemployment problems in industrial countries can be attributed to a significant extent to distortions in the labour market. These interventions have caused the level and structure of real wages to not adequately reflect the productivity of labour and the differences of skills in the labour force. Myriads of laws and regulations, most of which have been implemented in the course of creating the modern Welfare State, have made it very expensive for firms to hire labour, have made it unattractive for some employees to change jobs between firms or regions and have made it lucrative for others not to work. The purpose of this paper is to discuss the impact of government and trade union policies on the labour market and thus on employment. The analysis will focus on policies (i) directly influencing pay levels, (ii) directed toward job rights, (iii) concerned with job environment, and (iv)i dealing with social aspects.
Keywords: 330